Effect of Graded Levels of Nitrogen and Phosphorus on Yield and Nutrients Uptake .by Hybrid Fodder Sorghum under Rainfed Situation - Das, A; Jakasaniya, M S; Patel, K H; Patel, P T (Annals of Arid Zone, 2016)
A field experiment was conducted during the rainy season (kharij) of 1995 to 1997, to evaluate the response of hybrid fodder sorghum (variety GFSH- I) to graded levels of nitrogen and phosphorus fertilizers on Vertic Ustochrept of Bha! agroclimatic z’)ne in Gujarat. Individual effects of Nand P were significant on the fodder yield. Increasing nitrogen application from 0 to 20, 40 and 60 kg N ha’l gave increased green fodder yield by 56.7, 105.7 and 120.8% and dry fodder yield by 61.5, 117.3 and 128.8%, respectively, on pooled basis. Successive increase in phosphorus level from 0 to 10 and 20 kg P20S ha’l gave increased green fodder yield by 10.9 and 17.6% and dry fodder yield by 9.4 and 15.3%, respectively, on pooled basis. However, the fodder yield under 40 kg ha’l was at par with that under 60 kg N ha’J, while the yield under 10 kg P20S haÂ·1 was at par with that under 20 kg P20S haÂ·J. The effect of N on the uptake of N, P20S and K20 by fodder sorghum was significant in all the years. So far as net ICBR is concerned, 40 kg N haÂ·J was superior to 60 kg N haÂ·1 treatment, and 10 kg P20S ha’l was superior to 20 kg P20S haÂ·1 treatment. 40 kg N + 10 kg P20S haÂ·1 was found to be the optimal fertilizer dose.